1998
DOI: 10.1515/hfsg.1998.52.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Initiation and Progress in Wood Specimens Stressed in Tension. Part III. Clear Wood Specimens with Various Slopes of Grain

Abstract: Clear spruce wood specimens with 30, 20, 10, and 5° slope of grain were subjected to in-situ tensile failure tests in order to study fracture initiation and propagation. Fracturing of the specimens was carried out inside a SEM with a bending and a tension device, respectively. The bending and the tension specimens consisted of two to three growth rings. Fracture process in 30°-, 20°-, and 10°-specimens was quite uniform but differed from that of 5°-specimens. There was no difference between bending and tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Typical failures can be seen in Figure 28. Bodner, et al [71] and Galicki and Czech [80] experienced the same types of failure in their testing including separation at the earlywood-latewood boundaries. Bodner, et al [71] found that wood rays were structurally weak and were frequently the location of either initiation or discontinuity of fractures under tensile load.…”
Section: Relationship Of Shear Modulus and Shear Strengthmentioning
confidence: 84%
See 2 more Smart Citations
“…Typical failures can be seen in Figure 28. Bodner, et al [71] and Galicki and Czech [80] experienced the same types of failure in their testing including separation at the earlywood-latewood boundaries. Bodner, et al [71] found that wood rays were structurally weak and were frequently the location of either initiation or discontinuity of fractures under tensile load.…”
Section: Relationship Of Shear Modulus and Shear Strengthmentioning
confidence: 84%
“…Bodner, et al [71] and Galicki and Czech [80] experienced the same types of failure in their testing including separation at the earlywood-latewood boundaries. Bodner, et al [71] found that wood rays were structurally weak and were frequently the location of either initiation or discontinuity of fractures under tensile load. The knot samples failed in the deviated grain around the knots and frequently through the pith of the branch wood.…”
Section: Relationship Of Shear Modulus and Shear Strengthmentioning
confidence: 84%
See 1 more Smart Citation
“…Given that cell separation is governed primarily by lignin fracture, our results support this. Additionally, Bodner et al [ 22 , 23 ] showed that rays play an important role in wood fracture characteristics. Specifically, they showed that rays can act as stoppers for cracks propagating in the longitudinal direction (RL or TL).…”
Section: Discussionmentioning
confidence: 99%
“…Weiterhin konnte das Risswachstum durch die Zuwachslänge des Risses innerhalb eines feststehenden Intervalls zwischen zwei Aufnahmen beschrieben und dadurch einen Längenzuwachs pro Zeit ermittelt werden. Frühere Untersuchungen von B odner et al [8] hatten gezeigt, dass kurze Risse im Spätholz entstehen und im Frühholz enden, was auf die höhere Steifigkeit des Spätholzes gegenüber dem Frühholz zurückzuführen ist [9]. Diese Annahme konnte durch den Einsatz der fotooptischen Messtechnik überprüft und bestätigt werden.…”
Section: Lasteinleitungsversucheunclassified